A Review on Recent Developments and Prospects for the Oxygen Reduction Reaction on Hollow Pt‐alloy Nanoparticles. Issue 13 (8th May 2018) - Asset, Tristan; Chattot, Raphaël; Fontana, Marie; Mercier‐Guyon, Benjamin; Job, Nathalie; Dubau, Laetitia; Maillard, Frédéric
Abstract: Due to their interesting electrocatalytic properties for the oxygen reduction reaction (ORR), hollow Pt‐alloy nanoparticles (NPs) supported on high‐surface‐area carbon attract growing interest. However, the suitable synthesis methods and associated mechanisms of formation, the reasons for their enhanced specific activity for the ORR, and the nature of adequate alloying elements and carbon supports for this type of nanocatalysts remain open questions. This Review aims at shedding light on these topics with a special emphasis on hollow PtNi NPs supported onto Vulcan C (PtNi/C). We first show how hollow Pt‐alloy/C NPs can be synthesized by a mechanism involving galvanic replacement and the nanoscale Kirkendall effect. Nickel, cobalt, copper, zinc, and iron (Ni, Co, Cu, Zn, and Fe, respectively) were tested for the formation of Pt‐alloy/C hollow nanostructures. Our results indicate that metals with standard potential −0.4< E <0.4 V ( vs . the normal hydrogen electrode) and propensity to spontaneously form metal borides in the presence of sodium borohydride are adequate sacrificial templates. As they lead to smaller hollow Pt‐alloy/C NPs, mesoporous carbon supports are also best suited for this type of synthesis. A comparison of the electrocatalytic activity towards the ORR or the electrooxidation of a COads monolayer, methanol or ethanol of hollow and solid Pt‐alloy/C NPs underlines the pivotal role of the structural disorder of the metal lattice, and is supported by ab initio calculations. As evidenced by accelerated stress tests simulating proton‐exchange membrane fuel cell cathode operating conditions, the beneficial effect of structural disorder is maintained on the long term, thereby bringing promises for the synthesis of highly active and robust ORR electrocatalysts. Abstract : Defective is the new chic : Taking advantage of their highly defective structure (disordered surface, high polycrystallinity, contracted lattice, and open porosities), hollow Pt‐alloy/C nanoparticles can be used to achieve a high catalytic enhancement for both the oxygen reduction reaction and oxidation reactions such as CO oxidation or alcohol oxidation, thus opening the path to a generation of electrocatalysts designed around structural defects.